2021
DOI: 10.3390/molecules27010240
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Polyketide Metabolites from Penicillium bissettii and P. glabrum

Abstract: Screening of several fungi from the New Zealand International Collection of Microorganisms from Plants identified two strains of Penicillium, P. bissettii and P. glabrum, which exhibited antimicrobial activity against Escherichia coli,Klebsiella pneumoniae, and Staphylococcus aureus. Further investigation into the natural products of the fungi, through extraction and fractionation, led to the isolation of five known polyketide metabolites, penicillic acid (1), citromycetin (2), penialdin A (3), penialdin F (4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Recently, quite a lot of work has appeared on the isolation of penicillic acid from various sources, for example from Antarctic marine sediment or from various fungi of the genus of Penicillium [10,11]. Penicillic acid had antibacterial activity against Gram-positive and Gram-negative bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quite a lot of work has appeared on the isolation of penicillic acid from various sources, for example from Antarctic marine sediment or from various fungi of the genus of Penicillium [10,11]. Penicillic acid had antibacterial activity against Gram-positive and Gram-negative bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi of the genus Penicillium are widely studied as sources of bioactive compounds, but research on these fungi and their metabolites is far from complete, as shown in the work of Cadelis et al (2022) [14]. Studying P. bissettii and P. glabrum, this group isolated five known polyketide metabolites, penicillic acid, citromycetin, penialdin A, penialdin F and myxotrichin B.…”
mentioning
confidence: 99%
“…Fungi of the genus Penicillium are widely studied as sources of bioactive compounds, but research on these fungi and their metabolites is far from complete, as shown in the work of Cadelis et al (2022) [ 14 ]. Studying P. bissettii and P .…”
mentioning
confidence: 99%
See 1 more Smart Citation